Informing Migration Policies: A Data Primer - Calogero Carletto; Jennica Larrison; Caglar Ozden (Institute for the Study of Labor (IZA), 2014)
Researchers in many fields, such as demography, economics, and sociology, have established various data collection methodologies and principles to answer a range of academic and policy questions on migration. Although the progress has been impressive, some basic challenges remain. This paper addresses some basic, yet fundamental, questions on identification of international migrants and how their various demographic, personal, and human capital characteristics are captured via different data sources. The critical issues are the construction of proper sampling frames in censuses, registers, and surveys and the design of questionnaires in household, labor market, and other relevant surveys. The paper discusses how these data sources can be used to answer policy questions in areas such as labor markets, education, or poverty. The focus is on how some of the existing shortcomings in availability, quality, and relevance of migration data can be overcome via improvements in data collection methods.
Keywords: F22; J61; O15; 330; migration; development; survey design; data collection; data dissemination